Evaluation of Innovation in the Development of Agricultural Product Processing Industry Programs in Bantaeng Regency - Filial, Afrilyshiva; Susanti, Gita; Abdullah, Muhammad Tang (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2022)
Innovation evaluation consists of a systematic investigation to look at the various objectives of activities and programs, such as enabling learning, development, improvement and capacity, the importance of policies and programs and supporting oversight. This research method uses a qualitative approach and case studies toanalyze and explain phenomenawhich focuses on how to evaluate the innovation of the agricultural product processing industry development program. Data collection is done by conducting interviews and observations. Data processing and analysis techniques are carried out in three stages, namely: data reduction, presentation and drawing conclusions. Informants in this case are as follows: a). The research is as follows: Head of the Bantaeng Regency Agriculture Office. b). Secretary of the Bantaeng Regency Agriculture Office. c). Head of the Facilities and Infrastructure Division of the Bantaeng Regency Agriculture Service. d). CBO (Community Base Organization). The results showed that the framework used to measure the evaluation of innovation in the development of agricultural product industry programs in terms of program development, network expansion, and comprehensive system improvement was effective. Then the involvement of youth groups in socialization and counseling to women farmer groups was not involved. The new approach in evaluating the innovation of the agricultural product processing industry development program in Bantaeng Regency in terms of an economic approach and a social approach has been effective.